CULTURAL LEVEL – AN EXPRESSION OF CULTURAL DEVELOPMENT - Choriyev Sanjarbek Anvarovich (International Journal of Literature and Language Studies, 2026)
This article analyzes cultural level as an important indicator reflecting the degree of cultural development of both society and the individual. Cultural level is defined by a person’s ability to acquire and follow knowledge, values, traditions, art, and social norms. The study also highlights that the formation of cultural level is closely connected with education, upbringing, social environment, and mass media. It is argued that a culturally developed society can achieve stable development only when it has citizens with a high cultural level. Furthermore, it is emphasized that the improvement of cultural level strengthens tolerance, aesthetic taste, moral maturity, and social responsibility in society.